2020
DOI: 10.1136/esmoopen-2020-001075
|View full text |Cite
|
Sign up to set email alerts
|

First results of the EORTC-SPECTA/Arcagen study exploring the genomics of rare cancers in collaboration with the European reference network EURACAN

Abstract: PurposeRare cancers are defined by an incidence of <6 out of 100 000 cases per year. They are under-represented in clinical research including tumour molecular analysis. The aim of Arcagen is to generate a multinational database integrating clinical and molecular information of patients with rare cancers.Patients and methodsWe present the retrospective feasibility cohort of patients with rare cancers, with previously collected tumour samples available from any stage. Molecular analysis was performed using F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…For thymic malignancies, we were unable to confirm findings from TCGA as GTF2I was not part of any of the panels used in SPECTAlung and the sample size was very small. Moreover, we were also unable to repeats the molecular profile of the Arcagen studies (n = 23) for which several mutations were found in the RAS/RAF pathway 15 , similarly to what was found in the TCGA cohort. This clearly highlight the need for further fundamental and clinical research for rare cancers and possibly NGS panels adaptations.…”
Section: Discussionmentioning
confidence: 62%
“…For thymic malignancies, we were unable to confirm findings from TCGA as GTF2I was not part of any of the panels used in SPECTAlung and the sample size was very small. Moreover, we were also unable to repeats the molecular profile of the Arcagen studies (n = 23) for which several mutations were found in the RAS/RAF pathway 15 , similarly to what was found in the TCGA cohort. This clearly highlight the need for further fundamental and clinical research for rare cancers and possibly NGS panels adaptations.…”
Section: Discussionmentioning
confidence: 62%
“…These results are largely in line with the potential of broad molecular profiling in sarcoma patients that has been widely recognized previously. Actionable variants have been reported in 40–50% of sarcoma patients [ 30 , 31 ], germline variants are prevalent in 10–15% patients [ 7 ], and the utility of molecular profiling for accurate tumor classification has been established in previous clinical trials [ 4 , 5 ]. The extensive pathology testing to appropriately diagnose sarcoma patients is usually employed iteratively, while complete genomic characterization with WGS incorporates detection of all possible genomic events within one diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these and other similarly designed protocols have proven to be important "signal finding" endeavours from which interventional trials are increasingly emerging, including some that use composite biomarkers and evaluate combination therapies (ClinicalTrials.gov: NCT03127215, NCT04551521) [80]. In any case, progress in precision therapy of rare cancers, whether through interventional or registry studies, requires the consistent collaboration of multiple institutions in coordinated national networks or even international alliances such as the EORTC [81,82] and Cancer Core Europe [83].…”
Section: 3 Observational Registries and Cohort Studies The Recent Pas...mentioning
confidence: 99%